Students' Perception of Classroom Learning Environment in Physics Lessons & its Relation to Class Level of Study, Sex and Teachers' Degree of Knowledge about Constructivism Theory - El-Muhtaseb, Sumaya (Jordan Journal of Educational Sciences, 2005)
The aim of this study was to investigate secondary students' perceptions of learning classroom environment in physics lessons, and to identify the effects of class level, gender and teachers' degree of knowledge about the constructivist theory on these perceptions. A constructivist learning environment questionnaire was developed for the purpose of the study. The sample consisted of (733) students,The results showed that the sample mean is in the moderate level of conception. Moreover, there was a significant difference in students' perceptions regarding class level in favor of the first secondary class, and gender in favor of female students. Regarding the degree of teachers' knowledge, the results showed a significant difference between the three levels in favor of the constructivist and transitional theories. The results also showed, a significant difference regarding the interaction between the three variables. Consequently, several recommendations were proposed to improve the learning environment of the physics lessons